Analyse Et Evaluation Des Performance De la Modulation Multi porteuses Dans La Transmission d’information - CHERIFI ABDELHAMID (My University, 2017)
This thesis is part of hybrid systems of multi carrier modulation orthogonal OFDM / OCDMA- The division multiple access optical codes (OCDMA: Optical Code Division Multiple Access) broadband where bandwidth fiber is shared between multiple users. Such systems led to focus on the multiple access techniques already well known in radio frequency communication for sharing resources. The division multiple access optical codes (OCDMA) is now considered in this context as an attractive solution. However, in the optical domain, this technique has the disadvantages of being limited in terms of multiplexing capacity and suffer interference due to unwanted users (multiple access interference (MAI)), This is due to the non zero cross-correlation products of the codes used. In order to increase the number of users and data rate, and to reduce the impact of multi access interference (MAI), this study proposes the optical code division multiple access (OCDMA) systems with orthogonal frequency division multiplexing modulation (OFDM) based on a new zero cross correlation (ZCC) code. The OCDMA, a new ZCC-OFDM suggested system, was compared to the OCDMA-FCC (Flexible Cross Correlation)-OFDM in terms of signal to noise ratio (SNR) and bit error rate (BER). The results showed that the proposed system with the new ZCC code improves the system capacity performance by increasing the number of simultaneous users (cardinality) up to approximately 120% as compared to SCM (subcarrier multiplexing) OCDMA-FCC, and up to 7% in comparison to OCDMA-FCC (Flexible Cross Correlation)-OFDM. The adopted system has superior performance by saving around -3 dBm of power at the receiver with better bit error rate in comparison to OCDMA-FCC-OFDM system. In addition, the resulting power due to the increased number of users using our proposed new ZCC code is less in comparison to the FCC code. This improvement is due to the effect of the good auto/cross correlation properties of the new ZCC code.